Carbonate-coordinated cobalt co-catalyzed BiVO4/WO3 composite photoanode tailored for CO2 reduction to fuels. (July 2015) - Kim, Jin Hyun; Magesh, Ganesan; Kang, Hyun Joon; Banu, Marimuthu; Kim, Ju Hun; Lee, Jinwoo; Lee, Jae Sung
Abstract: We report here that cobalt carbonate (Co-Ci) is a tailored oxygen evolution electrocatalyst (OEC) from water on BiVO4 /WO3 composite photoanode to drive photoelectrochemical reduction of CO2 to fuels on a Cu cathode. For water oxidation, Co-Ci/BiVO4 /WO3 performed best in CO2 -saturated KHCO3 (KCi, pH 7) electrolyte recording an exceptional photocurrent of 3.5 mA/cm 2 at 1.23 VRHE under 1 sun illumination, and an onset potential of 0.2 VRHE . In the photoanode-driven CO2 reduction, the Co-Ci/BiVO4 /WO3 (photoanode)–Cu (cathode) system showed stable photocurrent and 51.9% faradaic efficiency (against water reduction to H2 ) for CO and C1 –C2 hydrocarbons, whereas the best known OEC cobalt phosphate (Co-Pi) was less stable and gave only 22.4% faradaic efficiency. Due to its high stability and CO2 reduction selectivity, the Co-Ci assisted system produced 11 times larger amount of CH4 than the Co-Pi assisted system in a continuous operation. Graphical abstract: A scheme of Co-Ci/BiVO4 /WO3 photoanode – Cu cathode system is shown for solar fuel production from H2 O and CO2 . The productivity of CH4 demonstrates unique effectiveness of carbonate-coordinated cobalt as a tailored oxygen evolution co-catalyst for the system. Highlights: Carbonate-coordinated cobalt (Co-Ci) on BiVO4 /WO3 photoanode applied for photoelectrochemical CO2 reduction cell. Co-Ci/BiVO4 /WO3 exhibited water oxidation activity comparable to the reported state-of-the-art values. In CO2 reduction on Cu cathode driven by the photoanode, stable and excellent yields of hydrocarbon fuels were achieved.